2021
DOI: 10.1029/2020jd034016
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Eyewall Replacement Cycles to Shortwave Radiation

Abstract: The sensitivity of tropical cyclone secondary eyewall formation (SEF) and subsequent eyewall replacement cycles (ERCs) to shortwave radiation is examined in this study by varying the solar constant and diurnal cycle at different times prior to an ERC using idealized simulations from the Weather Research and Forecasting model. The magnitude of shortwave radiation plays an important role in modifying the timing of the SEF with nonlinear interactions amplifying the SEF formation differences at longer lead-times. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…However, the ridding of the incloud‐warming still slows down the development of stratiform precipitation and decreased its coverage in the outer‐core region (Figure 11b). The delayed and weakened stratiform precipitation causes delayed SEF, which is similar to the results of Trabing and Bell (2021). The comparison between CTRL and NRAD60 further confirming that the development of stratiform precipitation associated with ORBs is the key dynamic process of CRF affecting SEF.…”
Section: Mechanismsupporting
confidence: 89%
See 3 more Smart Citations
“…However, the ridding of the incloud‐warming still slows down the development of stratiform precipitation and decreased its coverage in the outer‐core region (Figure 11b). The delayed and weakened stratiform precipitation causes delayed SEF, which is similar to the results of Trabing and Bell (2021). The comparison between CTRL and NRAD60 further confirming that the development of stratiform precipitation associated with ORBs is the key dynamic process of CRF affecting SEF.…”
Section: Mechanismsupporting
confidence: 89%
“…Radiation has profound influences on rainband convection and SEF, which is an important topic in TC dynamics. Previous studies revealed the multifaceted roles of shortwave radiation on the SEF (Tang et al., 2017; Trabing & Bell, 2021). This study probes into the horizontal heterogeneous distribution of radiative heating (mainly longwave) between the cloudy and the cloud‐free region (i.e., CRF) on SEF.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
See 2 more Smart Citations